Evolution of platelet activation parameters during septic shock in intensive care unit. (18th August 2022) - Vardon-Bounes, Fanny; Garcia, Cédric; Piton, Alexandra; Series, Jennifer; Gratacap, Marie-Pierre; Poëtte, Michaël; Seguin, Thierry; Crognier, Laure; Ruiz, Stéphanie; Silva, Stein; Conil, Jean-Marie; Minville, Vincent; et al.
Abstract: During severe sepsis, platelet activation may induce disseminate microvascular thrombosis, which play a key role in critical organ failure. Crucially, most of the studies in this field have explored platelet–leukocyte interactions in animal models, or explored platelets under the spectrum of thrombocytopenia or disseminated intravascular coagulation and have not taken into account the complex interplay that might exist between platelets and leukocytes during human septic shock nor the kinetics of platelet activation. Here, we assessed platelet activation parameters at the admission of patients with sepsis to the intensive care unit (ICU) and 48 hours later. Twenty-two patients were enrolled in the study, thirteen (59.1%) of whom were thrombocytopenic. The control group was composed of twelve infection-free patients admitted during the study period. The activation parameters studied included platelet-leukocyte interactions, assessed by flow cytometry in whole blood, as well as membrane surface and soluble platelet activation markers measured by flow cytometry and dedicated ELISA kits. We also investigated platelet aggregation and secretion responses of patients with sepsis following stimulation, compared to controls. At admission, the level of circulating monocyte-platelet and neutrophil-platelet heterotypic aggregates was significantly higher in sepsis patients compared to controls and returned to a level comparable to controls or even below 48 hours later. Basal levels of CD62P and CD63 platelet membrane exposure at admission and 48 hours later were low and similar to controls. In contrast, plasma level of soluble GPVI and soluble CD40 ligand was significantly increased in septic patients, at the two times of analysis, reflecting previous platelet activation. Platelet aggregation and secretion responses induced by specific agonists were significantly decreased in septic conditions, particularly 48 hours after admission. Hence, we have observed for the first time that critically ill septic patients compared to controls have both an early and durable platelet activation while their circulating platelets are less responsive to different agonists.